2003
DOI: 10.1074/jbc.m305110200
|View full text |Cite
|
Sign up to set email alerts
|

Human Caspase-7 Activity and Regulation by Its N-terminal Peptide

Abstract: Central to the execution phase of apoptosis are the two closely related caspase-3 and -7. They share common substrate specificity and structure, but differ completely in the sequence of their respective N-terminal regions including their N-peptides, a 23-28 residue segment that are removed during zymogen activation. We show that the N-peptide of caspase-7 plays no role in the fundamental activation or properties of the active protease in vitro. However, the N-peptide modifies the properties of caspase-7 in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(113 citation statements)
references
References 40 publications
9
104
0
Order By: Relevance
“…At first glance our data also point to caspase-3, and not caspase-7, as the primary executioner. There are several observations that support this idea: (i) caspase-3 activity is required for caspase-7 activation [50] and (ii) the generally higher concentrations of caspase-3 than caspase-7 in vivo. Although the last is not well defined, it has been shown, at least for the 293 human embryonic kidney cells, that intracellular caspase-3 concentration can be as high as 100-200 nM [51] and that of caspase-7 around 65 nM (H. Stennicke and G. Salvesen, personal communication).…”
Section: Discussionmentioning
confidence: 97%
“…At first glance our data also point to caspase-3, and not caspase-7, as the primary executioner. There are several observations that support this idea: (i) caspase-3 activity is required for caspase-7 activation [50] and (ii) the generally higher concentrations of caspase-3 than caspase-7 in vivo. Although the last is not well defined, it has been shown, at least for the 293 human embryonic kidney cells, that intracellular caspase-3 concentration can be as high as 100-200 nM [51] and that of caspase-7 around 65 nM (H. Stennicke and G. Salvesen, personal communication).…”
Section: Discussionmentioning
confidence: 97%
“…Removal of the prodomain of caspase-7 is required for its efficient activation in vivo, possibly because the highly charged N-terminal prodomain results in the physical sequestration of caspase-7 from its upstream caspase. 39 To our knowledge there has only been one earlier study to investigate the importance of the removal of prodomain of caspase-6 in cells. 40 They showed that the removal of the prodomain of caspase-6 was required both for caspase-8 processing and also for serum-depletion-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inherent cleavage site specificity of caspases have been applied to make active site probes that show some degree of selectivity for individual caspases, 10 and when these are coupled with selective antisera the identity of active caspases in complex mixtures is more readily disclosed. [11][12][13][14] Specificity for protein substrates Exosites. Having a preferred cleavage site specificity is not sufficient for proteolysis of natural proteins; appropriate presentation of the cleavage site seems critical for efficient hydrolysis.…”
Section: What It Takes To Be a Caspasementioning
confidence: 99%